CORRIGENDUM FOR 10.1210/en.2012-2130 (Endocrinology, 2016)
CONTEXT: Air pollution is a recognized risk factor for women's subfertility, yet its association with the timing of natural menopause remains understudied. OBJECTIVES: To examine the association between exposure to ambient air pollution and age at natural menopause (ANM). DESIGN AND SETTING: Longitudinal cohort study, the Study of Women's Health Across the Nation (SWAN), across six U.S sites (1999-2015). PARTICIPANTS: 1,457 midlife women aged 45-56 years from five racial/ethnic groups, after excluding those with hysterectomy or oophorectomy, or reproductive hormone use at baseline. METHODS: Annual exposures to PM2.5, NO2, and O3 were estimated using 1-km2 resolution data linked to residential addresses. Age at menopause was treated as a time-to-event outcome using accelerated failure time models to estimate the time ratios (TRs) and 95% confidence intervals (CIs). RESULTS: Women in the highest exposure quartile experienced natural menopause approximately one year earlier than those in the lowest quartile, with TRs (95% CIs) of 0.983 (0.971-0.995; p for trend=0.04) for NO2 and 0.983 (0.971-0.996; p for trend=0.004) for O3, whereas PM2.5 was not significantly associated with ANM. CONCLUSIONS: The approximately one-year earlier ANM among women exposed to the highest quartile of NO2 and O3 is comparable to the 0.8-year earlier menopause observed in current smokers relative to never smokers. These findings support the hypothesis that higher exposure to ambient air pollution is associated with an earlier onset of natural menopause.